(untitled) - Solomons, T. W. Graham (Hoboken, N.J., 2004)
This bestseller helps readers master basic skills with its clear and easy-to-follow presentation of key concepts. It focuses on the important ideas of organic chemistry and backs them up with illustrations and challenging problems. The authors' acclaimed writing style makes this thorny subject easy to grasp and comprehend. The new edition brings the book to the forefront of the latest research developments.
Keywords: Chemistry, organic,Hóa học, hữu cơ